Monitoring of adverse drug reactions is an important task of pharmacovigilance. Analysis of the regional department of State Expert Center of the Ministry of Health of Ukraine in Zaporizhzhia region - O. V. Kraydashenko; I. F. Belenichev; R. V. Stets; Yu. A. Kosogor; L. M. Kaptur (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Safety of medicines has always been, is and will be in the public interest as it relates to a wide range of issues related to drug treatment of almost all diseases, affects the vital activities of human and society existence. Analyzing the received reports we can determine medications and its doses, after taking which the side reactions occur most commonly, as well as which drugs’ combination potentiate the development of pharmacotherapy complications. Zaporizhzhia regional department of State Expert Center MoH of Ukraine received 714 reports of adverse reactions of drugs during 2016. Based on the analysis of spontaneous reports which available in Zaporizhzhia regional department of State Expert Center MoH of Ukraine, drugs that cause unexpected adverse reactions, can be placed in the next order: drugs for the treatment and prevention of infectious diseases, cardiovascular medicines, non-steroidal anti-inflammatory drugs, local anesthetics, hormone drugs, vitamin medicines, medicines that affect the function of the gastrointestinal tract, neurotropic drugs, antihistamine drugs, medicines that affect the function of the respiratory system, plasma substitutes and detoxification solutions.